MAIN CAUSES AND REGULARITIES OF COMMERCIAL FISH STOCK VARIATIONS - G. A. Sudakov (Юг России: экология, развитие, 2014)
The main cause of different quality of fish consists in changes in fish habitats including food supply. Variations in morphological quality of fish as well as in the age, size and sex composition show the population dynamics.Our knowledge of the main causes and regularities of commercial fish stock variability allows more substantiated approach to the assessment of parameters of fishing regulation and forecast.